Reconstructing The Meaning Of Hijab: A Hans-Georg Gadamer's Hermeneutical Analysis Of Abu Syuqqah's Viewpoint In The Book Tahrir Al-Mar’ah Fi ‘Asr Al- Risalah - Cholilach, Cholilach; Fata, Zidan Fathoni (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2025)
This article reexamines the construction of the meaning of hijab in Islam through Abu Syuqqah’s perspective in Tahrir al-Mar’ah fi ‘Asr al-Risalah using Hans-Georg Gadamer’s hermeneutic approach. Unlike interpretations that frame the hijab as a rigid obligation or symbol of restriction, Abu Syuqqah emphasizes its moral and ethical dimensions in social interactions, grounded in a contextual reading of Qur’anic verses al-Ahzāb (33:53, 59) and an-Nūr (24:31). He views the hijab not merely as clothing but as a social tool for preserving dignity while enabling women’s public roles. Employing Gadamer’s four hermeneutical concepts—historical consciousness, pre-understanding, fusion of horizons, and application—the study shows that Abu Syuqqah’s interpretation is shaped by his awareness of tradition, the Prophet’s social context, and contemporary challenges faced by women in Muslim societies. The article concludes that his reconstruction offers a form of social spirituality that integrates textual fidelity with contextual relevance, addressing both classical meanings and modern realities.